Chronic adiponectin deficiency leads to Alzheimer's disease-like cognitive impairments and pathologies through AMPK inactivation and cerebral insulin resistance in aged mice. Issue 1 (December 2016) - Ng, Roy; Cheng, On-Yin; Jian, Min; Kwan, Jason; Ho, Philip; Cheng, Kenneth; Yeung, Patrick; Zhou, Lena; Hoo, Ruby; Chung, Sookja; Xu, Aimin; Lam, Karen; et al.
Abstract Background Insulin resistance is the major pathogenesis underlying type 2 diabetes mellitus (T2DM) and these patients have doubled risk of Alzheimer's disease (AD). Increasing evidence suggests that insulin resistance plays an important role in AD pathogenesis, possibly due to abnormal GSK3β activation, causing intra- and extracellular amyloid-beta (Aβ) accumulation. Adiponectin (APN) is an adipokine with insulin-sensitizing and anti-inflammatory effects. Reduced circulatory APN level is associated with insulin resistance and T2DM. The role of APN in AD has not been elucidated. In this study, we aim to examine if adiponectin deficiency would lead to cerebral insulin resistance, cognitive decline and Alzheimer's-like pathology in mice. Methods To study the role of adiponectin in cognitive functions, we employed adiponectin-knockout (APN-KO) mice and demonstrated chronic APN deficiency in their CNS. Behavioral tests were performed to study the cognitions of male APN-KO mice. Brains and tissue lysates were collected to study the pathophysiological and molecular changes in the brain of APN-KO mice. SH-SY5Y neuroblastoma cell line was used to study the molecular mechanism upon APN and insulin treatment. Results Aged APN-deficient mice displayed spatial memory and learning impairments, fear-conditioned memory deficit as well as anxiety. These mice also developed AD pathologies including increased cerebral Aβ42 level, Aβ deposition, hyperphosphorylated Tau proteins, microgliosis and astrogliosis with increased cerebral IL-1β and TNFα levels that associated with increased neuronal apoptosis and reduced synaptic proteins levels, suggesting APN deficiency may lead to neuronal and synaptic loss in the brain. AD pathologies-associated APN-KO mice displayed attenuated AMPK phosphorylation and impaired insulin signaling including decreased Akt induction and increased GSK3β activation in the hippocampus and frontal cortex. Aged APN-KO mice developed hippocampal insulin resistance with reduced pAkt induction upon intracerebral insulin injection. Consistently, APN treatment in SH-SY5Y cells with insulin resistance and overexpressing Aβ induce higher pAkt levels through AdipoR1 upon insulin treatment whereas the induction was blocked by compound C, indicating APN can enhance neuronal insulin sensitivity through AMPK activation. Conclusion Our results indicated that chronic APN deficiency inactivated AMPK causing insulin desensitization and elicited AD-like pathogenesis in aged mice which also developed significant cognitive impairments and psychiatric symptoms.